Is It Worth It? Competing Routes and Hubs - Mehmet, Özay; Yorucu, Vedat (Springer, 2020)
The geopolitics of competing pipelines and new reserves of hydrocarbons in the Eastern Mediterranean region require evaluation with realism. The Greek Cypriot leadership must heed market forces and replace emotionalism with rational behaviour: Is it worth it to stubbornly follow exclusion politics and push non-viable projects? We say No. © 2020, Springer Nature Switzerland AG.
Keywords: Energy resources; Eastern Mediterranean; Market forces; Non-viable; Rational behaviours; Energy management